EFFECT OF EGG WEIGHT ON CHICK’S WEIGHT AND POST HATCHING GROWTH PERFORMANCE OF JAPANESE QUAIL (Coturnix coturnix japonica) - DUDUSOLA , I. O.; OSENI , S. O.; OLAWUMI , S. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
The effect of egg weight on chick body weight and post hatching growth performance of Japanese quail (Coturnix coturnix japonica) was studied. A total of 2575 eggs were collected and sorted into three groups by weight; light (<10g), medium (10–12 g) and heavy (>12 g). Egg weight (EW), Egg length (EL), Egg circumference (EC), Shank Length (SL) and Body weight (BW) were taken on the corresponding egg groups. Data was analyzed using PROC GLM of SAS® to compare percent fertility, hatchability, hatch and rearing mortality over three egg groups while relationship among recorded variables was estimated using the CORR procedure of SAS®. Results showed that there were significant (P<0.05) differences in egg weight, egg length and egg circumference among the three groups. Mean chick weights at hatching in light, medium and heavy eggs were 8.75g, 11.19g and 13.14g respectively. High positive phenotypic correlation was observed between body weight and shank length (R>0.50) indicating that an improvement in body weight could lead to an improvement in shank length and vice-versa. BW increased with SL within groups. Egg size and chick weight were positively correlated with growth performance traits. There were also significant differences between the egg weight groups with regards to percentage hatchability which was found to be 58.02%, 90.89% and 76.23% respectively, with the medium weight being superior also for fertility (94.57 %) and rearing mortality (1.53%). Medium sized eggs (10–12 g) were superior for hatchability, fertility and good quality day old chicks post hatching performance.